Dually Decorated Na3V2(PO4)2F3 by Carbon and 3D Graphene as Cathode Material for Sodium‐Ion Batteries with High Energy and Power Densities. Issue 19 (9th September 2020) - Hu, Lizhen; Cheng, Siqi; Xiao, Shunhua; Li, Wenna; Chen, Zhuo; Li, Wei; Huang, Bin; Liu, Qingquan; Chen, Quanqi
Abstract: The dually decorated Na3 V2 (PO4 )2 F3 by in‐situ formed carbon and three‐dimensional graphene (NVPF/C@3DG) is prepared via two hydrothermal steps and a high‐temperature calcination. Benefiting from the high electronic conductivity of carbon and 3DG, high surface area and the resulted high diffusion coefficients of Na +, NVPF/C@3DG displays superior electrochemical performance to the control NVPF/C. Between 2.5 and 4.5 V (vs. Na + /Na), NVPF/C@3DG presents the initial discharge capacity of 123.6 mAh g −1 at 0.2 C (25.6 mA g −1 ) and capacity retention of 92.1 % after 60 cycles, while NVPF/C shows initial discharge capacity of 119 mAh g −1 and capacity retention of 84.1 % under the identical test conditions. Even at 15 C, the initial discharge capacity and capacity retention after 1000 cycles of NVPF/C@3DG are as high as 91.2 mAh g −1 and 82.9 %, respectively, much better than the initial discharge capacity of 71.2 mAh g −1 and the corresponding capacity retention of 76.4 % for NVPF/C, respectively. Abstract : Double feature : Na3 V2 (PO4 )2 F3 /C@3DG was obtained via hydrothermal reaction of NaF with VPO4 /C@3DG, which was prepared by one hydrothermal step and high‐temperature calcination in inert atmosphere. Due to the high electronic conductivity of carbon and three‐dimensional graphene, high surface area and the resulted high diffusion coefficients of Na +, Na3 V2 (PO4 )2 F3 /C@3DG displays superior electrochemical performance to the control Na3 V2 (PO4 )2 F3 /C.